2018
DOI: 10.1002/ijc.31806
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the impact of an organised screening programme on cervical cancer incidence: A 26‐year study from northern Italy

Abstract: The impact of the organised cervical cancer (CC) screening programmes implemented in Europe since the 1990s has been insufficiently evaluated. We investigated the changes in CC incidence following the introduction of a screening programme in the Emilia-Romagna Region (northern Italy). The study period was 1988-2013. The programme, targeting women aged 25-64 years (1,219,000 in 2018), started in 1998. The annual incidence rates that would be expected in 1998-2013 in the absence of screening were estimated, firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…Cervical cytology has been used for cervical cancer screening for decades, and reduced the burden of cervical cancer worldwide. [1][2][3] Cytology-based cervical cancer screening is mostly performed through microscopic observation of cervical cell morphology by cytotechnologists or cytologists. [2][3][4] Cytology-based screening strategy is recommended for population-based cervical cancer screening in many guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cytology has been used for cervical cancer screening for decades, and reduced the burden of cervical cancer worldwide. [1][2][3] Cytology-based cervical cancer screening is mostly performed through microscopic observation of cervical cell morphology by cytotechnologists or cytologists. [2][3][4] Cytology-based screening strategy is recommended for population-based cervical cancer screening in many guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cytology-based cervical cancer screening is mostly performed through microscopic observation of cervical cell morphology by cytotechnologists or cytologists. [2][3][4] Cytology-based screening strategy is recommended for population-based cervical cancer screening in many guidelines. [5][6][7] Recently, human papillomavirus (HPV) test has being recommended for cervical cancer primary screening because of a slightly higher sensitivity, [5][6][7] and some countries are moving toward HPV test as primary screening or co-testing.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of endocervical adenocarcinomas has been proportionally increasing due to expansion of screening, particularly in population-based programs. 2 In the study by Stolnicu et al 3 , HPV-negative adenocarcinomas were diagnosed in more advanced stages than squamous carcinomas. Further studies are needed to clarify if this was due to later detection or a more aggressive behavior of the tumor.…”
Section: Conflicts Of Interestmentioning
confidence: 97%
“…An international cross-sectional study found that 38% of adenocarcinomas were not HPV-related. 2 A recently proposed histologic classification of endocervical adenocarcinoma, known as International Endocervical Adenocarcinoma Criteria and Classification (IECC), 3 uses the presence of HPVrelated disease to histologically classify cervical adenocarcinomas. Among nonhuman papillomavirus-associated adenocarcinoma (NHPVA), the authors identify the following histological types: endometrial, gastric-type, minimal deviation, serous, clear-cell and mesonephric.…”
mentioning
confidence: 99%
“…Recent studies of log-linear models in health analysis include Bucchi et al, (2019), Voumard et al, (2019), Gautam et al, (2019, Kamranrad et al, (2019), Lin et al (2019) and Wiseman et al, (2019). The last two have some relevance to poisoning: Mercury for Wiseman et al, (2019) and Asbestos for Lin et al, (2019).…”
mentioning
confidence: 99%